Cambridge O level Physics - Kennett, Heather (London : Hodder education, 2024)
The Cambridge O Level Physics book by Hodder Education is a detailed and well-organized textbook aimed at helping students prepare for the Cambridge O Level Physics exam. It is aligned with the Cambridge O Level Physics syllabus and provides in-depth explanations, practical examples, and numerous resources to aid in mastering key Physics concepts and performing well in the examination.
Keywords: Physics : O level